Variability in transport and biotransformation of cytarabine is associated with its toxicity in peripheral blood mononuclear cells. (April 2011) - Parmar, Sumit; Seeringer, Angela; Denich, Dina; Gäärtner, Franziska; Pitterle, Kai; Syrovets, Tatiana; Ohmle, Barbara; Stingl, Julia C
Aim: To adopt an individualized approach to assess cytarabine (ara-C) hematotoxicity, we studied the relationship between pharmacogenetic variability in the cytidine deaminase gene ( CDA ) and ara-C toxicity in native peripheral blood mononuclear cells from 100 healthy volunteers.Materials & methods: Peripheral blood mononuclear cells were incubated for 48 h with 3 µµM ara-C, and cell viability was analyzed by flow cytometry with and without the addition of an equilibrative nucleoside transporter transport inhibitor. CDA promoter and exonic variants were genotyped to derive haplotypes for the CDA gene.Results: Significant between-subject variability was observed in ara-C toxicity (21-fold with 40.1% coefficient of variation compared with 1.2-fold within-subject variability [9.6% coefficient of variation]). Inhibition of hENT1 reversed ara-C cytotoxicity. The linked CDA promoter variants -451C>T, -92A>G, -31Del and the exonic 79A>C variant were associated with ara-C toxicity (p < 0.05). CDA*2A haplotype was associated with ara-C toxicity (p = 0.03).Conclusion: Genetic polymorphisms within CDA may be risk factors for ara-C-induced hematotoxicity. Original submitted 6 October 2010; Revision submitted 29 November 2010.